2010
DOI: 10.1021/la1013889
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Nanofabrication Using Surface Forces

Abstract: We describe strategies to curve, rotate, align and bond precisely patterned two dimensional (2D) nanoscale panels using forces derived from a minimization of surface area of liquefying or coalescing metallic grains. We demonstrate the utility of this approach by discussing variations in template size, patterns and material composition. The strategy provides a solution path to overcome the limitation of inherently two dimensional lithographic processes by transforming 2D templates into mechanically robust and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 32 publications
0
72
0
2
Order By: Relevance
“…Gagler [21] and Gracias et al [23][24][25][26][27][28][29][30][31] showed that the surface tension of evaporating drop of liquid is sufficient to pull the walls of the photolithographically defined thin film patterns together and form various figures, such as boxes or pyramids with the size of several micrometers. These patterns typically consist of more rigid areas connected by thinner areas, which serve as hinges, when the thicker walls fold.…”
Section: Surface Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gagler [21] and Gracias et al [23][24][25][26][27][28][29][30][31] showed that the surface tension of evaporating drop of liquid is sufficient to pull the walls of the photolithographically defined thin film patterns together and form various figures, such as boxes or pyramids with the size of several micrometers. These patterns typically consist of more rigid areas connected by thinner areas, which serve as hinges, when the thicker walls fold.…”
Section: Surface Tensionmentioning
confidence: 99%
“…In addition to self-assembly of structures attached to the substrate, micro-origami figures disconnected from the substrate can serve as building blocks for meta-materials, where magnetic elements of the figures or surface tension at hydrophilic parts can be used to put these blocks together in two-or three-dimensional networks [26]. Here, tessellation methods of origami patterns can be used.…”
Section: Functionality Of the Micro-origami Structuresmentioning
confidence: 99%
“…The self-assembly of three dimensional objects on the micro-and nanoscale with any desired patterns based on surface force has been successfully demonstrated [77,78] and is potentially useful if coupled with micro-and nanofluidic applications. Ye et al has successfully combined microfabricated nanoliter scale fluidic devices with wireless technology by fabricating remote-controlled cubic microcontainers for temporal and spatial chemical delivery [37].…”
Section: Three Dimensional Metallic Microcontainermentioning
confidence: 99%
“…Ye et al has successfully combined microfabricated nanoliter scale fluidic devices with wireless technology by fabricating remote-controlled cubic microcontainers for temporal and spatial chemical delivery [37]. The gold-coated, nickel nanoliter containers were fabricated based on a combination of conventional microfabrication and self-assembly [77,78]. To facilitate chemical delivery, the containers were filled with a gel that was soaked in the chemical reagent to be released.…”
Section: Three Dimensional Metallic Microcontainermentioning
confidence: 99%
“…We leverage the advantages of planar lithography and combine them with self-folding methods 1-20 wherein physical forces derived from surface tension or residual stress, are used to curve or fold planar structures into three dimensional (3D) structures. In doing so, we make it possible to mass produce precisely patterned static and reconfigurable particles that are challenging to synthesize.In this paper, we detail visualized experimental protocols to create patterned particles, notably, (a) permanently bonded, hollow, polyhedra that self-assemble and self-seal due to the minimization of surface energy of liquefied hinges [21][22][23] and (b) grippers that self-fold due to residual stress powered hinges 24,25 . The specific protocol described can be used to create particles with overall sizes ranging from the micrometer to the centimeter length scales.…”
mentioning
confidence: 99%